PIK3CA Mutational Analysis of Parathyroid Adenomas. (13th April 2020) - Riccardi, Aaliyah; Lemos, Carolina; Ramos, Ryan; Bellizzi, Justin; Parham, Kourosh; Brown, Taylor C.; Korah, Reju; Carling, Tobias; Costa‐Guda, Jessica; Arnold, Andrew
ABSTRACT: Benign parathyroid adenoma is the most common cause of primary hyperparathyroidism, whereas malignant parathyroid carcinoma is exceedingly rare. Distinguishing parathyroid carcinoma from benign adenoma is often difficult, and may be considerably delayed even after surgical resection until the rigorous diagnostic criteria of local invasion of surrounding tissues and/or distant metastases are fulfilled. Thus, new insights into their respective molecular bases may potentially aid in earlier diagnostic discrimination between the two, as well as informing new directions for treatment. In two recent studies, gain‐of‐function mutations in PIK3CA, a recognized driver oncogene in many human malignancies, have been newly identified in parathyroid carcinoma. To assess the potential specificity for malignant, as opposed to benign parathyroid disease, of PIK3CA hotspot mutations, we PCR‐amplified and Sanger sequenced codons 111, 542/545, and 1047 and the immediate flanking regions in genomic DNA from 391 typical, sporadic parathyroid adenomas. Four parathyroid adenomas (1%) had subclonal, somatic, heterozygous, activating PIK3CA mutations. The rarity of PIK3CA activating mutations in benign parathyroid adenomas suggests that tumorigenic activation of PIK3CA is strongly associated with malignant parathyroid neoplasia. However, it does not appear that such mutations, at least in isolation, can be relied upon for definitive molecular diagnosis of parathyroid carcinoma. © 2020 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.